Efecto del mucílago de las semillas de lino (Linum usitatissimum L) como estabilizante en función a la concentración de néctar de manzana (Malus domestica) - Calapaqui Masapanta, Edison Rodrigo (2020)
This research work contains scientific information about five different methods of mucilage extraction from flax seeds (Linum usitatissimum L), it is proposed a new obtaining methodology considering the processes used by the authors; hydration of the seed 1:13, magnetic agitation at 60 °C for 5 h, precipitated with ethanol 96 °GL, centrifugation and lyophilization. In the same way of the studies investigated in relation to the stability and application of mucilage in drinks, nectars, there were detailed the physicochemical parameters such as: titratable acidity, °Brix, total solids, pH; microbiological analyses such as: molds, total coliforms, yeasts and organoleptic analyses are: flavor, color, smell and texture. Through research, some of the benefits of using mucilage were specified, as in the case of a saliva substitute to alleviate the sensation of dry mouth and thick saliva, creation of a nanoemulsion for diabetics replacing subcutaneous administration by the oral route, application in a pudding to reduce the acute postprandial peak of glucose and insulin and the risk of type 2 diabetes.